Investigation into performance of deep excavation in sand covered karst: A case report - Elbaz, Khalid; Shen, Shui-Long; Tan, Yong; Cheng, Wen-Chieh (Soils and foundations, 2018)
Performing deep excavations in karst regions is likely lead to geo-hazards, e.g. sinkholes, water ingress, and ground surface settlement. This case report presents the performance of a 16-m deep excavation in sand covered karst in Metro Line no. 9, Guangzhou, China. The performances during deep excavation, including lateral wall deflection, vertical wall movement, ground surface settlement, and settlement of adjoining buildings, were monitored and evaluated. Based upon the interpretation of the field measurements, the following major findings were obtained: (i) the lateral wall deflection and surface settlement measurements were smaller those cited in other case studies with similar geological conditions, (ii) both the grouting of the karst cavern and the use of the socket diaphragm wall panel dominated the performance of the deep excavation; (iii) the type of the founding structure could significantly affect the settlement development of the adjoining buildings. This case report provides insight into the design and construction of deep, narrow excavations in sand covered karst in a metropolitan environment.